RHYTHM CONTROL IN PATIENTS WITH BRADYASYSTOLIC ATRIAL FIBRILLATION - Miakinkova, L.O.; Liulka, Ye.M.; Katerenchuk, I.P.; Teslenko, Y.V.; Pysana, B.O. (World of Medicine and Biology, 2023)
Atrial fibrillation is the most common cardiac arrhythmia associated with thromboembolism, heart failure, depression, deterioration of quality of life, and reduced physical endurance. The rhythm control strategy is considered optimal in its treatment but is not always achievable. Right ventricular endocardial pacing is recommended for patients with bradycardic atrial fibrillation and preserved ejection fraction but can cause ventricular dyssynchrony. The aim of the study was to evaluate the effectiveness of implanting a dual-chamber pacemaker as an alternative method for sinus rhythm control in patients with long-standing bradysystolic atrial fibrillation and preserved ejection fraction, compared with single-chamber right ventricular pacing. Diastolic function, left atrial volume index, exercise tolerance, and quality of life were studied. Dual-chamber pacing is effective in rhythm control, and the severity of symptoms is reduced. Compared with single-chamber right ventricular pacing, there were decreased left atrial volume, tricuspid regurgitation rate, natriuretic peptide levels, increased exercise tolerance, improved quality of life indices, and reduced anxiety and depression.
Keywords: atrial fibrillation; heart failure; endocardial pacing; pacemaker; quality of life; exercise tolerance